2016
DOI: 10.1128/iai.00939-15
|View full text |Cite
|
Sign up to set email alerts
|

The LasB Elastase of Pseudomonas aeruginosa Acts in Concert with Alkaline Protease AprA To Prevent Flagellin-Mediated Immune Recognition

Abstract: eThe opportunistic pathogen Pseudomonas aeruginosa is capable of establishing severe and persistent infections in various eukaryotic hosts. It encodes a wide array of virulence factors and employs several strategies to evade immune detection. In the present study, we screened the Harvard Medical School transposon mutant library of P. aeruginosa PA14 for bacterial factors that modulate interleukin-8 responses in A549 human airway epithelial cells. We found that in addition to the previously identified alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 61 publications
1
79
0
1
Order By: Relevance
“…However, 78% of patients that underwent penetrating keratoplasty were infected with isolates harboring exoS. Along with the exotoxins, P. aeruginosa also produces several extracellular proteases of which alkaline proteases (aprA), elastase B (lasB) and protease IV (prpL) are often implicated in infections and helps the pathogen in immune evasion [46]. All the isolates investigated in this study were found to be positive for the genes lasB, aprA and prpL.…”
Section: Differential Expression Of T3ssmentioning
confidence: 75%
“…However, 78% of patients that underwent penetrating keratoplasty were infected with isolates harboring exoS. Along with the exotoxins, P. aeruginosa also produces several extracellular proteases of which alkaline proteases (aprA), elastase B (lasB) and protease IV (prpL) are often implicated in infections and helps the pathogen in immune evasion [46]. All the isolates investigated in this study were found to be positive for the genes lasB, aprA and prpL.…”
Section: Differential Expression Of T3ssmentioning
confidence: 75%
“…Importantly, we found AZM also induced premature transcripts in key transcriptional regulators of biofilm formation and virulence ( Supplementary Table S6). Such increases in premature transcript formation accompanied the downregulation of rpoS, rpoH, vqsR and anr [83][84][85]87,88,92]. Anr regulates QS and virulence gene expression in low-oxygen environments such as biofilms [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…In AZM treated biofilms ( Figure 3D), we observed reduced transcript levels of several global gene expression modulators associated with stress responses (rpoS [83,84], rpoH [85], and relA [86]), anaerobic metabolism (anr [87,88] Figure 3D). The expression of stress, virulence, biofilm, motility, and metabolism-related genes, many of which are controlled by these regulators, were also downregulated.…”
Section: The Effects Of Azm On P Aeruginosa Gene Expressionmentioning
confidence: 98%
See 1 more Smart Citation
“…LasR governs the production of the two proteases AprA and LasB. Both have previously been demonstrated to degrade flagellin (Bardoel et al, 2011;Casilag et al, 2015). Thus, it is conceivable that in tumours infected by the lasR mutant even more flagellin is present than in PA14 colonized tumours.…”
Section: Discussionmentioning
confidence: 99%